As Relações Padrasto e Enteado: aspectos psicodinâmicos - Marinho, Gláucia Souza Costa (2014)
This study aimed to identify the perceived stepfather about his relations with his ( s ) stepson ( s ) and i identify the perception stepfather about their function and role in the family . We used a clinical investigation of psychoanalytic theory that raised the data through semi - structured interviews and stories with family Drawing in 3 adults and stepfathers who were participants . The sessions were performed in an office setting , respecting technical and ethical issues in research and Psychology in particular , such as confidentiality and consent of the participants . The content analysis showed that there were peculiarities in each case studied , however , there were common factors in their actions and feelings about family and stepchildren : a) there was an ambiguity - for both men perceived themselves as providers and counselors of children and stepchildren , as there was also a perception that feelings by biological child were different from those experienced by stepchildren . b ) all stepfathers barriers in relations revealed by an unclear definition of its role and function within the family, often reinforced by wives , mothers , taken as those who hold the power over the child / stepchild , and this confusion generated rivalry stepfather and stepson in a dispute love of wife and mother . c ) the psychological point of view, it was observed that many conflicts referred them to the early stages of development , especially the Oedipal resolution as a reissue ; thus, the exercise of the function of stepfather gives the basis of the quality of their relationships with their parents in childhood - as occurs in the course of consanguineous parentage . So , the function of step father as well as the father is given by a rolling engagement. We suggest other work researches , because it was understood that this type of related developmental Psychology study can assist in health activities and prevention in mental health